2014
DOI: 10.4236/jss.2014.211003
|View full text |Cite
|
Sign up to set email alerts
|

Examining Characteristics of Resilience among University Students: An International Study

Abstract: Attending university is a particularly stressful time due to unique emergent stressors such as changes in environment, loss or diminishment of social support networks, academic pressures, developing peer relationships, and financial management. There is growing recognition that these common stressors may have deleterious effects on the mental health of students. Resilience, a personality characteristic that moderates the negative effects of stress and promotes adaptation, has been associated with increased psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
78
0
16

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(99 citation statements)
references
References 43 publications
5
78
0
16
Order By: Relevance
“…In fact, as literature has indicated, transitions are a source of stress where individuals leave the familiar network behind, entering into an unfamiliar territory (Latham & Green, 1997). Besides, the academic pressure university students are exposed to, can have a negative effect on their mental health (Pidgeon et al, 2014). Indeed, mental illness rates are above general population rates when undergraduates get to their second year of university (Macaskill, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, as literature has indicated, transitions are a source of stress where individuals leave the familiar network behind, entering into an unfamiliar territory (Latham & Green, 1997). Besides, the academic pressure university students are exposed to, can have a negative effect on their mental health (Pidgeon et al, 2014). Indeed, mental illness rates are above general population rates when undergraduates get to their second year of university (Macaskill, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…También, la resiliencia, la ansiedad rasgo, y su interacción predicen significativamente la respuesta al tratamiento después de ajustar por la edad y la duración del tratamiento; así niveles bajos de ansiedad rasgo y niveles altos de resiliencia podrían contribuir a una mejor respuesta al tratamiento en pacientes deprimidos . Pidgeon, Rowe, Stapleton, Magyar, & Lo (2014), detectaron en una muestra de estudiantes universitarios, como aquellos que presentaban puntuaciones más bajas en los niveles de resiliencia experimentaron niveles más altos de trastornos psicológicos (depresión, ansiedad y estrés), en comparación con los estudiantes universitarios con altos niveles de resiliencia; resultados similares encontraron Yu et al (2009), en una muestra pacientes con VIH: un nivel bajo de resiliencia se asocia con depresión, ansiedad y estrés. Además, diversos estudios, hacen patente el efecto moderador de la resiliencia en la gravedad de los síntomas de estrés postraumáti-co (Ben-Zur & Gilbar, 2011;Pietrzak et al, 2010;Wingo et al, 2010).…”
Section: Resiliencia Y Salud Mentalunclassified
“…Several studies revealed that hardiness, optimism, and self-confidence proved to be effective in mitigating stress among 158 university lecturers in Csech Republic (Paulik, 2001) [172] ; hope, optimism, self-efficacy and resilience contributed decrease in stress among employees (Avey et al, 2009) [9] , and increased the work engagement (Avey, et al, 2008). Further, high levels of resilience have significantly lower level of psychological distress (Pidgeon, et al, 2014) [176] All of these positive coping traits which can be termed as human internal resources greatly depend on individual"s personality which is also dependent on one"s heredity, experience, culture, and environment (Apruebo, 2009) [3] . However, some traits can be transferred and enhanced through social learning and insights.…”
Section: Utilizing Positive Coping Traitsmentioning
confidence: 99%